ANALYSIS of INTERFERENCE PATTERN of the FIBER INTERFEROMETER as a MOTION SENCOR - Ahmed, Duraid H.; Jasim, Fathi M.; Mohammed, Musab S. (Iraqi Journal of Science, 2020)
The production and analysis of an optimal interference pattern for the optical fiber interferometer of a 193.1THz continuous laser source was simulated by comparing the spectral spectroscopy of the two arms of interferometer to be used as a heterodyne detection in sensing the body range, speed, and direction of movement by delaying the time between the arms. The study showed that the fringe pattern can be sensed a range by the free spectral range FSR and the velocity by the fringe separation FS and the direction by the fringe spatial frequency FSF.